PETA JALAN INDUSTRI HALAL DI INDONESIA UPAYA MENINGKATKAN DAYA SAING GLOBAL - Vera Ayu Oktoviasari; Iva Ashari Ananda; Mukhtar Lutfi (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
The halal industry roadmap involves strengthening stakeholders involved in the development of the halal industry in Indonesia, including institutional development involving the government/authorities, consumers and business actors. With the existence of a road map for the development of the halal industry and its consistent and sustainable implementation, it is possible that Indonesia will become a major player in the world's halal industry in the future and develop competent Human Resources (HR) in their fields through the development of the Indonesian National Work Competency Standards (SKKNI) which includes halal auditors. , halal supervisor, halal chef, halal slaughterer, halal manager. This research uses qualitative research using library research. Research results, development projections in several priority sectors as well as harmonization of institutions related to halal guarantees, improvements in infrastructure, services and services as well as improvements in human resources will have an impact on both national and global competitiveness. Data shows that total trade in Indonesian halal products in the January-October 2023 period reached USD 53.43 billion. Of this amount, exports of Indonesian halal products were recorded at USD 42.33 billion and imports at USD 11.10 billion